Evaluasi Penggunaan Listrik dengan Metode Konservasi Energi untuk Efisiensi Energi di Gedung FKIP UNTIRTA - Fahrizal Tunjung Kresnadi (Sekolah Tinggi Teknik PLN, 2020)
Knowing the level of intensity of energy consumption (IKE) in the FKIP Untirta building using the energy audit method for achieving energy efficiency. The data used in data collection in the form of electricity usage data, building area data and observations made by researchers. Analysis of the data used in this study is to use the formula of energy consumption intensity. The results showed the IKE value of the CB FKIP Untirta building was 254.5 kWh/m2. With these results, it can be seen that the IKE value in the CB FKIP Untirta building is still inefficient. This is based on ASEAN-USAID parameters which range at 240 kWh/m2. Based on electrical energy consumption in the CB FKIP Untirta building there is an opportunity for energy saving or energy saving solutions that are replacing TL lamps with Led lights or by replacing TL lamps that are smaller watts and in terms of air conditioning or air conditioning load replacing R32 refrigerant with R32 refrigerant mixture and The R290 has proven to be quite efficient in terms of savings and energy efficiency. And the duration of use of electrical energy.